Relación entre la migración interregional y el nivel de ingresos en Ecuador, año 2018 - Salinas Armijos, Karen Yessenia (2023)
In Ecuador, in 2018, interregional migration accounted for 40.5% of Ecuadorians who reside in a place other than their place of birth, and therefore the receiving place is the urban area, which brings greater imbalances to the area of residence. In this sense, the present research has the general objective of determining the relationship between interregional migration and the level of income in Ecuadorian society in 2018. The data were extracted from the National Institute of Statistics and Census (INEC, 2018) from the survey of employment, unemployment, and underemployment, for which techniques such as descriptive statistics, and propensity score matching (PSM) were used. As the main findings, a strong relationship was obtained between the variables of migration and income, since both, people with high and low incomes migrate for economic reasons, some in search of work, obviously those with low incomes, while people with high incomes their work requires mobility in them. In addition to this, policies should be defined to support the mainstreaming of migration into local development, that is, to have a more inclusive approach and mitigate inequalities in rural areas and support the implementation and proper monitoring of public investment projects.